1995
DOI: 10.1002/bdd.2510160807
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of terbinafine and of its five main metabolites in plasma and urine, following a single oral dose in healthy subjects

Abstract: The plasma pharmacokinetics, and the urinary excretion, of terbinafine and its five main metabolites have been investigated after a single oral dose administration of 125 mg to 16 healthy subjects. In plasma, the highest concentrations are observed for the two carboxybutyl metabolites, with a predominance for the carboxybutylterbinafine. For this metabolite, as compared to terbinafine, the Cmax and AUC are 2.4 and 13 times higher respectively. The demethylterbinafine presents a plasma profile close to that of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
3

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 11 publications
1
23
3
Order By: Relevance
“…58 At least seven cytochromes P450 (CYP) appear to be responsible for metabolizing terbinafi ne into more than 15 metabolites. 59 In adults, the N-demethyl and carboxybutyl metabolites constitute the largest fraction of the metabolites observed. Maximum circulating concentrations and total body exposure are comparable or in excess of those observed with the parent compound.…”
Section: Clinical Pharmacology (Tables 1 and 2)mentioning
confidence: 99%
“…58 At least seven cytochromes P450 (CYP) appear to be responsible for metabolizing terbinafi ne into more than 15 metabolites. 59 In adults, the N-demethyl and carboxybutyl metabolites constitute the largest fraction of the metabolites observed. Maximum circulating concentrations and total body exposure are comparable or in excess of those observed with the parent compound.…”
Section: Clinical Pharmacology (Tables 1 and 2)mentioning
confidence: 99%
“…Our group uses P. carinii f. sp. carinii (6,13). In limited studies, we have found no differences in drug susceptibility among genetically different strains of rat P. carinii (8).…”
mentioning
confidence: 70%
“…Using an ATP cytotoxicity assay to screen candidate anti-P. carinii drugs, our group found that terbinafine has a 50% inhibitory concentration of 3.7 g/ml against rat P. carinii at 72 h (16). Although this concentration indicates moderate activity on our rating scale (7, 28), it exceeds levels of terbinafine in serum that can be achieved in humans (1 to 2 g/ml) or rodents (2 to 2.5 g/ml) with oral administration of the drug (9,13,15,18,19,20). Here we have analyzed the efficacy of terbinafine in our mouse and rat models of pneumocystosis.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Terbinafine is highly lipophilic and keratophilic, so it is extensively distributed throughout adipose tissue, dermis, epidermis, and nails in humans (12,19). The apparent volume of distribution in humans is relatively large and has been reported to be in the range of 780 to 2,000 liters (22,25,27,28,33). The large volume of distribution of terbinafine and its accumulation in peripheral tissue as well as the slow redistribution of the drug into blood are likely to significantly influence the half-life of terbinafine.…”
mentioning
confidence: 99%